Building A Portfolio Under Economic Uncertainty - Nia, Vera Mita; Siregar, Hermanto; Sembel, Roy; Zulbainarni, Nimmi (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study explores how the returns and volatility of stocks, gold, bonds, and Bitcoin (BTC) respond to movements in inflation, interest rates (SBI), and exchange rates. To capture inter-asset relationships, the Granger Causality Test was applied, while GARCH modeling was used to evaluate hedging behavior under normal market conditions. An investment portfolio was then formulated using the Arbitrage Pricing Model (APT), comprising 28% stocks, 16.28% gold, 26.76% bonds, and the remaining proportion in BTC, delivering an estimated return of 0.0178 with optimized risk. The dataset covers monthly trading activity from 2018 to 2023 as in-sample observations, with an additional seven months used for out-of-sample validation. The results reveal that BTC returns correlate with those of gold and bonds, while stock volatility shows a link to BTC volatility. Gold consistently serves as a hedge against macroeconomic variables, whereas bonds primarily act as a portfolio diversifier. These findings underscore the relative stability of gold and bonds as instruments for risk mitigation against BTC’s inherent volatility. Viewed through a sustainability lens, incorporating gold and bonds into the portfolio enhances resilience, lowers systemic risk, and supports long-term financial sustainability, aligning investment strategies with responsible and stable wealth management.